2020
DOI: 10.1186/s12916-019-1487-2
|View full text |Cite
|
Sign up to set email alerts
|

A landscape of genomic alterations at the root of a near-untreatable tuberculosis epidemic

Abstract: Background: Atypical Beijing genotype Mycobacterium tuberculosis strains are widespread in South Africa and have acquired resistance to up to 13 drugs on multiple occasions. It is puzzling that these strains have retained fitness and transmissibility despite the potential fitness cost associated with drug resistance mutations. Methods: We conducted Illumina sequencing of 211 Beijing genotype M. tuberculosis isolates to facilitate the detection of genomic features that may promote acquisition of drug resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“… 8 , 10 , 11 , 13 , 21 23 , 26 58 Additionally, a technical report published by WHO was identified and included ( figure 1 ). 19 QUADAS-2 assessment of the clinical studies showed that the risk of bias was unclear for 19 (68%) of 28 studies 19 , 22 , 23 , 26 , 29 , 30 , 32 , 33 , 39 , 44 , 46 49 , 52 , 53 , 55 , 56 , 58 due to a possible absence of masked interpretation of mutations; risk of bias was high for 11 studies 23 , 27 , 28 , 32 , 35 , 40 , 43 , 44 , 47 , 48 , 53 that used a phenotypic DST method not approved by WHO ( appendix 1 pp 3–7). According to the QUADAS-2 assessment, the level of concern regarding applicability was classified as high for six (21%) of the 28 clinical studies 23 , 35 , 45 , 48 , 49 , 51 because they did not report on both atpE and Rv0678 genes.…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 10 , 11 , 13 , 21 23 , 26 58 Additionally, a technical report published by WHO was identified and included ( figure 1 ). 19 QUADAS-2 assessment of the clinical studies showed that the risk of bias was unclear for 19 (68%) of 28 studies 19 , 22 , 23 , 26 , 29 , 30 , 32 , 33 , 39 , 44 , 46 49 , 52 , 53 , 55 , 56 , 58 due to a possible absence of masked interpretation of mutations; risk of bias was high for 11 studies 23 , 27 , 28 , 32 , 35 , 40 , 43 , 44 , 47 , 48 , 53 that used a phenotypic DST method not approved by WHO ( appendix 1 pp 3–7). According to the QUADAS-2 assessment, the level of concern regarding applicability was classified as high for six (21%) of the 28 clinical studies 23 , 35 , 45 , 48 , 49 , 51 because they did not report on both atpE and Rv0678 genes.…”
Section: Resultsmentioning
confidence: 99%
“…(4) Liu et al [27] provided 44 SNPs specific to Modern Beijing strains. (5) South African strain of Asia Ancestral 1 (AA1SA) [35]. (6) Mestre et al [19] Bmyc scheme is based on the presence/absence pattern of SNPs in genes involved in replication, recombination and repair.…”
Section: Strain Typing Schemesmentioning
confidence: 99%
“…Reports describing the presence of bedaquiline and clofazimine resistance in southern Africa (defined as the countries of the Southern African Development Community) have been scarce. 12 , 13 In this study, we present genotypic and phenotypic data for M tuberculosis isolates with RAVs identified from our clinical report 11 and other unpublished (to date) cohort studies at the Africa Health Research Institute, and report a more extensive microbiological investigation of bedaquiline and clofazimine MICs to investigate the extent of cross-resistance. To better understand the phylogenetic and geographical distribution of bedaquiline and clofazimine RAVs in southern Africa, we then analysed a comprehensive collection of our own and publicly available whole-genome sequencing data.…”
Section: Introductionmentioning
confidence: 99%